Will a warmer and wetter future cause extinction of native Hawaiian forest birds?. (29th September 2015) - Liao, Wei; Elison Timm, Oliver; Zhang, Chunxi; Atkinson, Carter T.; LaPointe, Dennis A.; Samuel, Michael D.
Abstract: Isolation of the Hawaiian archipelago produced a highly endemic and unique avifauna. Avian malaria ( Plasmodium relictum ), an introduced mosquito‐borne pathogen, is a primary cause of extinctions and declines of these endemic honeycreepers. Our research assesses how global climate change will affect future malaria risk and native bird populations. We used an epidemiological model to evaluate future bird–mosquito–malaria dynamics in response to alternative climate projections from the Coupled Model Intercomparison Project. Climate changes during the second half of the century accelerate malaria transmission and cause a dramatic decline in bird abundance. Different temperature and precipitation patterns produce divergent trajectories where native birds persist with low malaria infection under a warmer and dryer projection (RCP4.5), but suffer high malaria infection and severe reductions under hot and dry (RCP8.5) or warm and wet (A1B) futures. We conclude that future global climate change will cause significant decreases in the abundance and diversity of remaining Hawaiian bird communities. Because these effects appear unlikely before mid‐century, natural resource managers have time to implement conservation strategies to protect this unique avifauna from further decimation. Similar climatic drivers for avian and human malaria suggest that mitigation strategies for Hawai'i have broad application to human health.